Human T-cell leukemia virus type 1 (HTLV-1) and adult T-cell leukemia: insights into cellular transformation - Jeang, Kuan-Teh (Henry Stewart Talks, 2007)
HTLV-1 epidemiology, Virus infectivity of T lymphocytes, Description of adult T-cell leukemia, Details of mechanisms used by virus for oncogenesis
Archived at 2018/10/28